2012
DOI: 10.1007/s00417-012-2065-x
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma in penetrating keratoplasty: risk factors, management and outcome

Abstract: Careful and ongoing observation of IOP, especially in the first year after PK, is recommended for patients after penetrating keratoplasty and prompt treatment of IOP elevation when indicated. Early filtering surgery with a better outcome than other surgery procedures should be preferred if medical treatment is not sufficient. Despite anti-glaucoma therapy, good visual outcome can remain beyond expectations despite a clear graft. While there is a potential option for graft exchange, damage to the optic nerve fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 44 publications
3
56
1
Order By: Relevance
“…The prevalence of traumatic IOP elevation and glaucoma after PKP is known to be elevated, ranging between 11 and 48%, [20][21][22][23][24] and is perhaps particularly elevated in eyes after penetrating eye injury. 25 Mechanisms for IOP elevation after PKP include postoperative edema and inflammation compromising the trabecular meshwork, angle scarring, peripheral anterior synechiae, retained viscoelastics, and steroid response.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of traumatic IOP elevation and glaucoma after PKP is known to be elevated, ranging between 11 and 48%, [20][21][22][23][24] and is perhaps particularly elevated in eyes after penetrating eye injury. 25 Mechanisms for IOP elevation after PKP include postoperative edema and inflammation compromising the trabecular meshwork, angle scarring, peripheral anterior synechiae, retained viscoelastics, and steroid response.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ITC (11-29%) was less than in other studies after PK (56%, 96.8%) [16,21,22], but in these studies not only cases of FED and BK were analysed. Nonetheless, our data showed that PAS in cases of FED are significantly associated with the development of post-keratoplasty glaucoma, not only in eyes after PK but also in eyes after DSEK (p = 0.01) [7,17,18,19,20,21].…”
Section: Discussionmentioning
confidence: 85%
“…- Post-keratoplasty glaucoma, iatrogenic-induced secondary glaucoma, was defined as a durable elevated IOP ≥22 mm Hg at different time points that resulted in the introduction of anti-glaucoma medication or surgical intervention [14,16,17]. In patients with pre-existing glaucoma, worsening of the IOP control requiring additional medication or surgery was necessary for the diagnosis of post-keratoplasty glaucoma [14,16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations